Dorsal and ventral language pathways in persistent developmental stuttering. (August 2016) - Kronfeld-Duenias, Vered; Amir, Ofer; Ezrati-Vinacour, Ruth; Civier, Oren; Ben-Shachar, Michal
Abstract: Persistent developmental stuttering is a speech disorder that affects an individual's ability to fluently produce speech. While the disorder mainly manifests in situations that require language production, it is still unclear whether persistent developmental stuttering is indeed a language impairment, and if so, which language stream is implicated in people who stutter. In this study, we take a neuroanatomical approach to this question by examining the structural properties of the dorsal and ventral language pathways in adults who stutter (AWS) and fluent controls. We use diffusion magnetic resonance imaging and individualized tract identification to extract white matter volumes and diffusion properties of these tracts in samples of adults who do and do not stutter. We further quantify diffusion properties at multiple points along the tract and examine group differences within these diffusivity profiles. Our results show differences in the dorsal, but not in the ventral, language-related tracts. Specifically, AWS show reduced volume of the left dorsal stream, as well as lower anisotropy in the right dorsal stream. These data provide neuroanatomical support for the view that stuttering involves an impairment in the bidirectional mapping between auditory and articulatory cortices supported by the dorsal pathways, not in lexical access and semantic aspects of language processing which are thought to rely more heavily on the left ventral pathways.